2001
DOI: 10.1103/physrevb.64.172201
|View full text |Cite
|
Sign up to set email alerts
|

Cooling-rate dependence of the density ofPd40Ni10Cu30

Abstract: The effect of cooling rate on the density of the Pd 40 Ni 10 Cu 30 P 20 bulk metallic glass ͑BMG͒ have been investigated by over the cooling rate range from 0.63 to 500 K/s. The cooling rate dependence of density, microhardness and thermal properties of the BMG is determined. Based on the thermal-expansion coefficients measured in the amorphous and supercooled liquid states, respectively, it is deduced that the density of the BMG in the ''ideal'' state approaches that of its crystalline counterpart. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 18 publications
(11 reference statements)
3
25
0
Order By: Relevance
“…Structural analysis reveals no crystallization: all voxels return to an amorphous, vitrified state, although the rapid quenching reduces the amount of short-range icosahedral order initially present [28]. The properties of metallic glasses depend upon the quench rate used during their synthesis [45][46][47]. Thus, we investigate whether the properties of the rapidly quenched material in TSs match those of equilibrium liquids quenched at the same rate.…”
Section: Sqzsmentioning
confidence: 88%
“…Structural analysis reveals no crystallization: all voxels return to an amorphous, vitrified state, although the rapid quenching reduces the amount of short-range icosahedral order initially present [28]. The properties of metallic glasses depend upon the quench rate used during their synthesis [45][46][47]. Thus, we investigate whether the properties of the rapidly quenched material in TSs match those of equilibrium liquids quenched at the same rate.…”
Section: Sqzsmentioning
confidence: 88%
“…In the classical picture, nucleation is considered to take place in a solution of ions that has become supersaturated, leading to the nucleation of the solid phase by stochastic solute clustering, and the earliest crystal precursor is considered to be a cluster of critical size (14,15). Because of the stochastic formation mechanism, such metastable clusters are a rare species.…”
Section: Stable Prenucleation Calcium Carbonate Clustersmentioning
confidence: 99%
“…This has been the basis for recent theoretical studies (12,13) of structural models of metallic glasses, in which a correlation between compositions having especially dense packing and compositions that are known to quench to the glassy state at relatively low cooling rates was sought, but not obtained. Earlier studies of the density of glasses, based on the Archimedes method, have been mostly limited to relatively narrow compositional ranges of ternary and quaternary alloys with large critical sample sizes for glass formation (14)(15)(16), and no correlation between density and the ease of glass formation has been demonstrated.…”
mentioning
confidence: 99%
“…As discussed in literature, glass formation ability (GFA) of BMGs is best described by the critical cooling rate, R c [1-3]. In addition to its role as one of the decisive factors in the vitrification process of BMGs, the cooling rate also influences the final microstructure [4,5] and physical properties [6]. Both theoretic and experimental results have directly shown that mechanical properties of BMGs were closely related to cooling rates applied during the sample preparation process [7,8].…”
mentioning
confidence: 97%